al-Tasāʾulāt wa-al-Asʾilah fī al-Islām wa-Ahammiyyatuhā - Shaibu, Abdul-Baasit; Bin Jamil, Khairil Husaini (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study explores the concept of questioning in Islam and its significance from both religious and linguistic perspectives, highlighting its crucial role in acquiring knowledge, decision-making, and social interaction. The research problem arises from the need to understand Islam’s stance on questioning, particularly given the existence of Quranic verses and Prophetic traditions that both encourage and discourage it. This apparent contradiction necessitates a thorough examination to determine when questioning is praiseworthy and when it is reproachable. The study’s significance lies in offering a balanced perspective that enables Muslims to utilize questioning effectively without transgressing religious boundaries while also enriching Islamic studies related to jurisprudence and inference. Employing an analytical and inductive methodology, the research collects and examines scriptural texts and scholarly opinions to derive well-founded conclusions. The findings indicate that although purposeful and constructive questioning remains an essential component in the Islamic educational framework, command, need, concern, and benefit are concepts required of the questioner when practicing questioning in order to make the resulting questions praiseworthy. These concepts ensure that through preventing the questioner from unnecessary self-burdening, stubbornness, or merely testing his interlocutor or making a mockery of him or any such reprehensible and undesirable traits. It also demonstrates the relation between necessities, needs, and improvements as understood and used in the field of the Maqāsid al-Sharee’ah and the four concepts required of a praiseworthy questioner.